2012
DOI: 10.1089/lap.2011.0057
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Models for Pediatric Minimally Invasive Surgical Training—A Template for the Future

Abstract: Pediatric minimally invasive surgery is a rapidly developing field with a steep learning curve for each new procedure that is developed and integrated into practice. The European consensus is that the training across the learning curve should not be on the patients. Simulation is a widely accepted methodology to shorten the learning curve. Training on animal models is an advanced form of simulation. This helps to reduce morbidity and the costs of patient care. This article describes our 3 years of experience i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Numerous training models outside of the operating room exist that have been shown to provide excellent training opportunities. 35,36 Two-and three-dimensional training models ranging from simple shoebox-setups 37 to animal models 36,38 have been proposed and evaluated to increase exposure to MIS and help surgeons acquire the necessary skills outside of the operating room. 39 Studies have demonstrated that MIS skills -especially the training of intracorporal suturing and knottying in simulator settings-successfully transfer to the operating room, 36,40 suggesting that some of the early phase of the learning curve can be achieved outside of the OR and consequently minimize the effect of the learning curve on the patient's outcome.…”
Section: Trainees 31 Consultants 12mentioning
confidence: 99%
“…Numerous training models outside of the operating room exist that have been shown to provide excellent training opportunities. 35,36 Two-and three-dimensional training models ranging from simple shoebox-setups 37 to animal models 36,38 have been proposed and evaluated to increase exposure to MIS and help surgeons acquire the necessary skills outside of the operating room. 39 Studies have demonstrated that MIS skills -especially the training of intracorporal suturing and knottying in simulator settings-successfully transfer to the operating room, 36,40 suggesting that some of the early phase of the learning curve can be achieved outside of the OR and consequently minimize the effect of the learning curve on the patient's outcome.…”
Section: Trainees 31 Consultants 12mentioning
confidence: 99%
“…The literature reports its extensive use to develop surgical experiences both in conventional and minimally invasive surgery given the similarities between the model and the human anatomy. 10 Still, the dimensions of the porcine model do not adequately comply with the anatomic characteristics of newborns and young children. 11 On the other hand, rabbit is a useful animal model for ability formation and surgical training of pediatric residents.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of TEF are described [52], although work is ongoing to replace the need for bovine or other animal components with synthetic materials to improve availability, avoid the intrinsic ethical difficulties, and potentially reduce cost [51]. It remains to be seen if MIS will supplant traditional open surgery for TEF given concerns of intraoperative carbon dioxide retention and potential for higher anastamotic complications.…”
Section: Simulators In Pediatric Surgerymentioning
confidence: 99%